Upland rice weeds of South and Southeast Asia - Galinato, Marita I. (IRRI, 1999)
To provide a practical identification guide and information on biology and mangement for the major weeds of upland rice across Asia. Tit was produced as an output of the Upland Rice Research Consortium, a collaborative research partnership between IRRI and upland rice research groups in bangladesh, India, Indonesia, lao PDR....Many upland weeds are common across these countries, and it was thought that such a book would be useful to help in the struggle to develop better intergrated weed management systems.